Identificación de mastitis subclínica en leche cruda, por el método de ultrasonido en fincas del municipio de Popayán (Cauca) (2021)
In the present thesis, a study was carried out that leads us to the detection of Subclinical mastitis in Bovine cattle through the implementation of a non-invasive and unconventional system such as ultrasound, which works through waves that are measured and correlated with the speed of sound, this in order to contribute something advanced and technified within the present diagnostic methods for this disease. The analysis areas for the project corresponded to farms located in the plateau of the city of Popayán Cauca. 31 samples were analyzed with the Ultrasound method, which is based on the speed of the wave generated and expelled by an oscilloscope on the milk present to be sampled, taking into account that to choose which milk to perform the analysis, a test was first carried out with the conventional method of CMT California mastitis test; and then we continue to corroborate the analysis by this Ultrasound method. The analysis and the results obtained allow us to compare them with other results obtained of a more advanced type such as the somatic cell count (CCS) and depending on the comparison, we could define whether the non-invasive method Conventional Ultrasound is effective for the detection of subclinical mastitis. Within the results, a likelihood of 1434 and 1556 m / s and a flight time between 5791 and 6947 m / s were obtained. Indicating us. Thus, the non-invasive-unconventional ultrasound method does not generate effective diagnostic differences with respect to conventional methkods. Keywords: ultrasound, subclinical mastitis, somatic cell count, cow